THE EFFECT OF THE SCHOOL LITERACY MOVEMENT ON INCREASING THE READING INTEREST OF GRADE III ELEMENTARY SCHOOL STUDENTS: PENGARUH GERAKAN LITERASI SEKOLAH TERHADAP PENINGKATAN MINAT BACA SISWA KELAS III SEKOLAH DASAR - Chelsie Austa; Fitriyeni (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The low interest in reading of students is still a fundamental problem in the world of education in Indonesia. Although the School Literacy Movement (GLS) has been implemented in various educational units, its implementation has not fully shown optimal results. This study aims to determine the influence of the School Literacy Movement on the reading interest of grade III students at SD Negeri 85 Pekanbaru. The study used a quantitative approach with an ex post facto design, in which the researcher did not provide a direct treatment, but analyzed the relationship between the independent variable (GLS) and the bound variable (students' reading interest). The research sample was 31 students. Data were analyzed using validity, reliability, descriptive statistics, normality tests, and simple regression analysis with the help of the SPSS 25 for Windows program. The results of the study show that all items of the instrument are declared valid and reliable with values. The results of a simple regression analysis showed that the School Literacy Movement had a significant effect on students' reading interest with a significance R Square value of 0.000 < 0.05. This means that GLS contributes 60.3% to the increase in students' reading interest, while 39.7% is influenced by other factors such as family support and literacy facilities. The implications of this study show that the success of the implementation of GLS does not only depend on the routine of reading activities, but also on the support of a conducive learning environment, a variety of interesting reading materials, and the role of teachers and parents in fostering a literacy culture at school and at home.